2020
DOI: 10.1186/s12913-020-05548-0
|View full text |Cite
|
Sign up to set email alerts
|

Claims data analysis of medical specialist utilization among nursing home residents and community-dwelling older people

Abstract: Background: Most older people, and especially those in need of long-term care, suffer from one or more chronic diseases. Consequently, older people have an increased need of medical care, including specialist care. There is little evidence as yet whether older people with greater medical care needs obtain adequate medical care because existing studies do not sufficiently control for differences in morbidity. In this study we investigate whether differences in medical specialist utilization exist between older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
8
0
2
Order By: Relevance
“…AOK consists of 11 regional health-care funds and together they represent the largest SHI fund in Germany. With 27 million insured persons, around one-third of the entire German population is covered by AOK (AOK-Bundesverband 2022 ; Schulz et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…AOK consists of 11 regional health-care funds and together they represent the largest SHI fund in Germany. With 27 million insured persons, around one-third of the entire German population is covered by AOK (AOK-Bundesverband 2022 ; Schulz et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Das Projekt wurde mit Mitteln des Innovationsausschusses beim Gemeinsamen Bundesausschuss unter dem Förderkennzeichen 01VSF16039 gefördert. Teilergebnisse des Projekts wurden bereits veröffentlicht [ 13 , 14 ]; ein Gesamtbericht des Projekts mit weiteren Analysen auf Basis dieser Daten wird nach Ende des Projekts durch den Mittelgeber veröffentlicht.…”
Section: Methodikunclassified
“…Zwar weisen Pflegebedürftige mehr Hausarztkontakte auf als Nichtpflegebedürftige [ 8 ]; ob diese allerdings fachärztliche Kontakte ersetzen können, ist fraglich. Lediglich hinsichtlich der neurologischen Versorgung zeigt sich bei Pflegebedürftigen eine höhere Inanspruchnahme, selbst wenn für die Tatsache kontrolliert wird, dass Pflegebedürftige mehr neurologische Erkrankungen aufweisen als Nichtpflegebedürftige [ 13 ]. Darüber hinaus konnte gezeigt werden, dass es mit höherer Pflegestufe umso wahrscheinlicher ist, bei einer Erkrankung keinen entsprechenden Facharztkontakt zu haben [ 14 ].…”
Section: Hintergrundunclassified
“…Most nursing home residents suffer from multimorbidity, frailty, cognitive impairments, and polypharmacy, all of which necessitate access to and utilization of medical care [4][5][6][7]. In nursing homes, almost all residents have regular contact with general practitioners (GPs) [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This is surprising, since nursing home residents usually have high dental care needs resulting from poor oral health, which is negatively associated with quality of life [14][15][16][17]. Moreover, it has been shown that, with the exception of neurologists and psychiatrists, the proportion of individuals having contact with medical specialists at least once per year is lower among nursing home residents than among community-dwelling elderly [4,5], and contact rates also vary widely among nursing homes [10,11]. However, the influence of nursing home characteristics has not been studied in detail so far.…”
Section: Introductionmentioning
confidence: 99%